Mattering; changing the narrative in secondary schools for youth who truant. (3rd July 2021) - Baskerville, Delia
ABSTRACT: Truancy in schools is a serious long-term unresolved educational issue that positions youth who truant as outsiders. This narrative about youth positioning developed over time. Data from a grounded theory, qualitative study is used to indicate how a sample of thirteen youth who truant in New Zealand explained their truancy experiences outside classrooms. Findings show that with peer support and care, youth were able to reposition themselves, matter and be who they wanted to be in these safe, chosen spaces. This article will support educators, counsellors and youth workers to consider these outside classroom experiences and provide the necessary connection for youth to matter and reengage in education.